Format of emergency department electronic health records in Europe. The European initiative and the eCREAM proposal - Bertolini, Guido; Ghilardi, Giulia Irene; Pandolfini, Chiara; Bacchiega, Alessandro; Catania, Felice; Magnini, Bernardo; Mitro, Peter; Notas, George; Prosen, Gregor; Sharma, Pankaj; Górka, Jacek; Nattino, Giovanni (Frontiers in Disaster and Emergency Medicine, 2025)
The lack of cross-border patient health data exchange in Europe is an obstacle in many ways and can negatively affect patient care and health. When clinicians have incomplete information about patients traveling or residing abroad, for example, continuity of care cannot be assured, potentially leading to poorer health outcomes. The European Electronic Health Record Exchange Format (EEHRxF) is a system being established in Europe to permit the interoperability of different healthcare systems, such as electronic health records (EHRs) and medical devices, so that they can share data to support patient care and research. The system is currently being introduced for electronic prescriptions and dispensations, patient summaries, which are part of the larger collection of health data known as the electronic health record, laboratory results and medical imaging studies and their reports, and hospital discharge reports. In emergency medicine, where research is challenging due to time and resource constraints, the EHR should no longer be seen solely as a tool to support clinical practice; it is also a source of valuable information to fuel research and improve patient care. The use of data for research, one of the stated secondary goals of the EEHRxF, thus becomes paramount here and deserves to be properly developed. It is in this context that the eCREAM (enabling Clinical Research in Emergency and Acute care Medicine through automated data extraction) project, a 5-year Horizon Europe project, was established. eCREAM will develop a system to exploit EHRs to enable research and improve decision-making, resource allocation and patient outcomes. It will address this target in two ways. First, by creating a new EHR that simultaneously meets clinical and research needs, collecting reliable, structured data that facilitate the clinical process and are readily usable for research purposes. Second, by developing an advanced natural language processing tool tailored to the specific needs of emergency medicine to automatically extract accurate, structured data from the free texts contained in EHRs. The project's innovative approach addresses current challenges in data extraction and utilization and sets a new standard for emergency medicine in Europe in the digital age. This article provides a general overview of the eCREAM project.